Leverage digital tools in construction project during the pandemic and transition to endemic - Khoo, Yee Leng (2023)
The Covid-19 pandemic has wreaked havoc across all sectors, with the construction industry being one of the hardest hits. The escalation of ramifications on construction projects has been noteworthy, highlighting the urgency for further research into the adoption of digital tools during the pandemic and the transition to an endemic phase. However, the majority of prior research have solely focused on the impacts of Covid-19 on the construction industry and the strategies to mitigate them. Thus, the aim of this research is to investigate the adoption of digital tools in the construction project during the Covid-19 pandemic and the transition to the current endemic. The objectives are to identify the types of digital tools leveraged in construction project during the pandemic and the transition to the current endemic, to explore the potentials of digital tools implementation in construction project during the pandemic and the transition to the current endemic and to uncover the barriers of the digital tools adoption in construction project during the pandemic and the transition to the current endemic. This research employed a quantitative research approach utilising questionnaire surveys that were participated by 135 construction practitioners hailing from the Klang Valley area in Malaysia. Through a thorough literature review, ten digital tools, eleven potentials and eleven barriers were identified and further examined in this research. Overall, the top 3 most widely adopted digital tools are Cloud Computing, BIM and Drone. Meanwhile, the top 3 most recognized potentials of these tools are “I adopt cloud computing to promote my project’s communication and collaboration”, “I adopt BIM to enhance my project’s site planning and management” and “I adopt BIM, AR and VR to enhance my project design”. However, the finding revealed that there is a moderate correlation between the respondents’ recommendation and adoption level of digital tools The low level of adoption may be ascribed to 3 primary barriers, namely lack of top management support, organization culture and substantial initial investment. In short, this research has the potential to advance comprehension of the current level of digital tool adoption and the notable obstacles impeding their implementation, thereby facilitating improved readiness to combat pandemics or unanticipated occurrences in the future.